Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có: \(\frac{54}{195}-\frac{1}{2}=\frac{108}{390}-\frac{195}{390}\)
\(=-\frac{87}{390}=-\frac{29}{130}\)
Vậy \(\frac{54}{195}-\frac{1}{2}=-\frac{29}{130}\)
\(5-1,5-1\frac{1}{2}\)
=\(5-1,5-1,5\)
=\(5-\left(1,5+1,5\right)\)
=\(5-3\)
=\(2\)
\(\left(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{9.10}\right).100-\left[\frac{5}{2}:\left(x+\frac{266}{100}\right)\right]:\frac{1}{2}=89\)
\(\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{9}-\frac{1}{10}\right).100-\left[\frac{5}{2}:\left(x+\frac{266}{100}\right)\right]:\frac{1}{2}=89\)
\(\left(1-\frac{1}{10}\right).100-\left[\frac{5}{2}:\left(x+\frac{266}{100}\right)\right]:\frac{1}{2}=89\)
\(90-\left[\frac{5}{2}:\left(x+\frac{266}{100}\right)\right]:\frac{1}{2}=89\)
\(\left[\frac{5}{2}:\left(x+\frac{266}{100}\right)\right]:\frac{1}{2}=1\)
\(\frac{5}{2}:\left(x+\frac{266}{100}\right)=\frac{1}{2}\Rightarrow x+\frac{266}{100}=5\Rightarrow x=\frac{117}{50}\)
Vậy x = 117/50
Ta có:
\(\left(\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{9.10}\right).100\\ =\left(\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{9}-\frac{1}{10}\right).100\)
\(=\left(1-\frac{1}{10}\right).100\)
\(=\frac{9}{10}.100\)
= 90
Khi đó đề bài sẽ thành : \(90-\left[\frac{5}{2}:\left(x+\frac{266}{100}\right)\right]:\frac{1}{2}=89\)
\(\Rightarrow\left[\frac{5}{2}:\left(x+\frac{266}{100}\right)\right]:\frac{1}{2}=1\)
\(\Rightarrow\frac{5}{2}:\left(x+\frac{266}{100}\right)=\frac{1}{2}\)
\(\Rightarrow x+\frac{266}{100}=5\)
\(\Rightarrow x=\frac{117}{50}\)
Vậy \(x=\frac{117}{50}\)
\(2\frac{4}{3}+\frac{4}{12}=\frac{2.3+4}{3}+\frac{4}{12}=\frac{10}{3}+\frac{4}{12}=\frac{40}{12}+\frac{4}{12}=\frac{44}{12}=\frac{11}{3}\)
\(2\frac{4}{3}=\frac{10}{3}\)
\(\frac{10}{3}+\frac{4}{12}=\frac{120}{36}+\frac{12}{36}\)
\(=\frac{132}{36}=\frac{22}{6}=\frac{11}{3}\)
\(đổi9\frac{3}{2}=\frac{21}{2}\)
\(\frac{9}{2}+\frac{21}{2}=\frac{30}{2}=15\)
\(=15\)
\(12\frac{4}{5}\)=\(\frac{64}{5}\).
Ta có :
\(\frac{64}{5}+\frac{4}{5}=\frac{68}{5}\)
\(12\frac{4}{5}+\frac{4}{5}=\frac{64}{5}+\frac{4}{5}=\frac{68}{5}\)
Đáp số cuối cùng là 89%
\(\frac{89}{100}=89\) o/o